MORPHOLOGICAL, CYTOLOGICAL AND PALYNOLOGICAL FEATURES OF THREE CLOSELY RELATED CENTAUREA SPECIES (ASTE RACEAE) FROM TURKEY - Bancheva, Svetlana; Kaya, Zafer; Binzet, Riza (State Natural History Museum Nas Ukraine, 2014)
This study was carried out to determine the main distinctive morphological, cytological and palynological features of three closely related Centaurea L. taxa (Asteraceae) growing in Turkey: C. aytugiana Bancheva, Kaya et Binzet, C. stenolepis Kerner and C. salicifolia M. Bieb. ex Willd. The first species, recently described from Karabuk province, Turkey (Bancheva et al. 2014), is an endemic of Karabuk province, whereas the remaining taxa have larger distribution ranges. The results show that the morphological (including pollen-morphological) traits and chromosome numbers proved to be of high diagnostic value and are very useful for determination.
Keywords: Asteraceae; Centaurea; Endemic Species; Chromosome Number; Pollen Morphology; Sem